DETERMINAN KEPATUHAN WAJIB PAJAK USAHAWAN TERHADAP PENERIMAAN PAJAK - Widyanti, Yeni; Wahasusmiah, Rolia (Fakultas Ekonomi Universitas IBA, 2020)
Tax acceptance is the biggest contribution for the country. The increase of tax acceptance can be achieved by one of them is from the income tax payer obtained. Income tax can be obtained one of them from the private sector whose tax subject is entrepreneurs. However, in achieving targeted tax receipts, there is a need to prevent compliance with taxpayers to fulfill its obligations. This research is a type of quantitative study aimed at testing taxpayers ' compliance variables with income level indicators, confidence level, knowledge level, taxpayer awareness, and Fiskus quality of service. The results of this study indicate that the income level is negative and insignificant to the tax receipt, while the taxpayer confidence level has a positive effect on the tax receipt, the taxpayer knowledge level is not Tax receipt, the taxpayer's awareness has a positive effect on the tax receipt, and the quality of the Fiscus service does not affect the tax acceptance.